2013
DOI: 10.1121/1.4820798
|View full text |Cite
|
Sign up to set email alerts
|

Audio-visual speech experience with age influences perceived audio-visual asynchrony in speech

Abstract: Previous research indicates that perception of audio-visual (AV) synchrony changes in adulthood. Possible explanations for these age differences include a decline in hearing acuity, a decline in cognitive processing speed, and increased experience with AV binding. The current study aims to isolate the effect of AV experience by comparing synchrony judgments from 20 young adults (20 to 30 yrs) and 20 normal-hearing middle-aged adults (50 to 60 yrs), an age range for which a decline of cognitive processing speed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 47 publications
12
33
0
Order By: Relevance
“…Taken together the studies by Hay-McCutcheon et al (2009) and Baskent and Bazo (2011) may indicate an influence of AV experience on AV asynchrony detection in speech, and by controlling for age differences in hearing acuity and cognitive processing speed the findings of Alm and Behne (2013) strengthen this assumption. Cognitive processing speed changes little until 60 years of age (e.g., Der and Deary, 2006), and the results of Alm and Behne's study (2013) revealed that normal-hearing middle-aged adults (mean 53 years) had a significantly more conservative ALT than normal-hearing young adults (mean 23 years), whereas the VLTs were similar between the age-groups.…”
Section: Introductionsupporting
confidence: 68%
See 3 more Smart Citations
“…Taken together the studies by Hay-McCutcheon et al (2009) and Baskent and Bazo (2011) may indicate an influence of AV experience on AV asynchrony detection in speech, and by controlling for age differences in hearing acuity and cognitive processing speed the findings of Alm and Behne (2013) strengthen this assumption. Cognitive processing speed changes little until 60 years of age (e.g., Der and Deary, 2006), and the results of Alm and Behne's study (2013) revealed that normal-hearing middle-aged adults (mean 53 years) had a significantly more conservative ALT than normal-hearing young adults (mean 23 years), whereas the VLTs were similar between the age-groups.…”
Section: Introductionsupporting
confidence: 68%
“…ALT and VLT indicate the participants' synchrony threshold for audio-lead and visual-lead stimuli and the distance between ALT and VLT is the AV synchrony window. Studies on SJ generally reveal an AV synchrony window of a few hundred milliseconds (e.g., Alm and Behne, 2013;Conrey and Pisoni, 2006;Hay-McCutcheon et al, 2009) with ALT substantially more conservative than VLT (e.g., Alm and Behne, 2013;Conrey and Pisoni, 2006;Hay-McCutcheon et al, 2009). Previous research reveals considerable diversity within normal populations for both RT (e.g., Besle et al, 2004;Der and Deary, 2006;Hale et al, 1988) and AV asynchrony detection (e.g., Conrey and Pisoni, 2006;Powers et al, 2009).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…From a cognitive perspective, this may well reflect the activation of topdown processes for speech. This again might imply that the anticipation building up when observing the culmination of a physical event cannot compete with the years of training most people possess when it comes to predicting the next syllable in a stream of speech [1]. With respect to media providers, the relative intolerance to asynchrony in our selected speech excerpt serves as a reminder for particular caution when it comes to preserving synchrony for this type of content.…”
Section: Resultsmentioning
confidence: 99%